Comparative Assessment of Radioactive Contamination in APR 1400 Reactor During SBO and TMI Accidents - Ghaderinia, F.; Rahgoshay, M.; Jafari, J. (Atom Indonesia, 2026)
An alternative approach to estimate the tissue phantom ratio (TPR) at depths of 20 cm and 10 cm (TPR₂₀,₁₀) under non-reference conditions is required to address situations where a 10 × 10 cm² field size is not achievable on a specific linear accelerator (LINAC) during a beam quality test. This study aims to estimate the TPR20,10 under non-reference conditions using a geometric sequence approach, and to compare it with the TPR₂₀,₁₀ under non-reference conditions estimated using the Sauer method, the Palmas method, a linear fit approach, as well as with the TPR₂₀,₁₀ under reference conditions calculated using the TRS-398 protocol. The first step in this study was measuring the percentage depth dose (PDD), D20cm, and D10cm with field size variations from 4 × 4 cm² to 10 × 10 cm² for both 6 MV and 10 MV X-ray beams. The PDD were used to estimate the TPR₂₀,₁₀ using a geometric sequence approach, the Sauer method, the Palmans method, and a linear fit approach, and to calculate the TPR₂₀,₁₀ using the TRS-398 protocol. The D20 cm and D10 cm were also used to calculate the TPR₂₀,₁₀ using the TRS-398 protocol. The TPR₂₀,₁₀ for 6 MV and 10 MV X-ray beams estimated using the geometric sequence approach were 0.683 ± 0.004 and 0.742 ± 0.005, respectively. The level of precision that could be reached by the geometric sequence approach is potentially equivalent to the TRS-398 protocol, the Sauer method, the Palmans method, and the linear fit approach. The TPR₂₀,₁₀ for 6 MV and 10 MV X-ray beams estimated using the geometric sequence method did not show a significant difference compared with the TPR₂₀,₁₀ calculated using the TRS-398 protocol. However, the TPR₂₀,₁₀ for 6 MV and 10 MV X-ray beams estimated using the geometric sequence approach showed a significant difference compared with those TPR₂₀,₁₀ estimated using the Sauer method and the Palmans method.